(3eYQaI CReGf MUhd GdCTcGd GdYGQVI ddchGcHs - (3Ydj Hf bOGeI GdHZOGOj, CHh GdMSfs
(3ChdgG (B:s
(3bGd CeG HYO agPg QSGdI cJHJgG dHYV GdCUMGH ai eYQaI CReGf MUhd GdCTcGd GdYGQVI ddchGcH ai MQcGJgG s
(3BNQgG (B:s
(3GdCTcGd GdeNJdaI ebSheI Ydi cd hCUZQ gPg GdCbSGe eecfI GdMUhd ai eYQaI GdJi jecf MUhdgG ef GdJbGhje ddCjGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3edi edc (B- (3WgQGf (B(640) s
Keywords: (3Gdadcs